Corporate Governance Country Assessment : Zambia - World Bank (Washington, DC, 2012)
Good corporate governance ensures that companies use their resources more efficiently, protects minority shareholders, leads to better decision making, and improves relations with workers, creditors, and other stakeholders. It is an important prerequisite for attracting the patient capital needed for sustained long-term economic growth. This report provides an assessment of Zambia's corporate governance policy framework. It highlights recent improvements in corporate governance regulation, makes policy recommendations, and provides investors with a benchmark against which to measure corporate governance in Zambia. Tapping the potential of capital markets and professionalizing boards and management will require reform efforts to continue. The companies act should be revised and harmonized with the securities act. Revisions should be accompanied by an analysis of lessons learned from the recently revised companies act in the UK. Stakeholders should consider moving explicit protection against unfair related party transactions into the Code, and revising the non-financial disclosure framework for listed companies. The Lusaka Stock Exchange (LuSE) and its stakeholders should then consider revisions to the code and further develop the LuSE website as a primary source of information about listed companies. The Securities and Exchange Commission (SEC) should continue to build its enforcement capacity, and to establish corporate governance enforcement priorities. More support and resources should be provided by the public and private sector to the Institute of Directors of Zambia.